1986
DOI: 10.1038/icb.1986.29
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study and Computer Simulation of the Turnover of Choline in Erythrocytes of Patients Treated With Lithium Carbonate

Abstract: Summary.The mechanism by which choline accumulates in erythrocytes during treatment with lithium salts has been elucidated. A component of the study was a kinetic description of erythrocyte phospholipase-D, which catalyses the release of intracellular choline from phospholipids. Apparent steady-state kinetic parameters for calcium ions were determined: K^ (± SD) = 0-6 ± 0'3 mmol/1 aqueous cell volume and V^,^ (± SD) =12 + 4 iimo\/\ packed red blood cells (RBC) min"'. Competitive inhibition of the phospholipase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…. Since then, !H NMR studies of red blood cells have provided information of clinical interest as well as detailed information about the biochemistry of red blood cells (5, 6,13, [33][34][35][36][37][38][39][40][41][42][43][44][45]. NMR measurements of intact red blood cells offer unique possibilities for clinical analysis.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Since then, !H NMR studies of red blood cells have provided information of clinical interest as well as detailed information about the biochemistry of red blood cells (5, 6,13, [33][34][35][36][37][38][39][40][41][42][43][44][45]. NMR measurements of intact red blood cells offer unique possibilities for clinical analysis.…”
Section: Applicationsmentioning
confidence: 99%
“…For example, the concentrations of freely mobile metabolites and other small molecules in the intracellular region can be determined directly, the rates of selected enzymatic processes can be measured, and intracellular pH can be determined. Clinical applications will be illustrated by the determination of choline in red blood cells (37,40,41,45)', free choline accumulates in red blood cells of manic-depressive patients taking lithium carbonate.…”
Section: Applicationsmentioning
confidence: 99%
“…ATM kinase is a major regulator of the DNA damage response, and the activation of ATM upon DNA damage involves multiple cascade reactions, including acetylation 41 , UFMylation 42 and destabilization of linker histone H1.2 32 . In this study, we confirmed the presence of m6A modifications on ATM mRNA by MeRIP.…”
Section: Discussionmentioning
confidence: 99%
“…Although cellular phospholipid content and composition change with cell age, the levels are influenced by lipid uptake from the blood plasma and by ester exchange reactions. The uptake of PC from the plasma via high-density lipoprotein (HDL) is well documented and characterized [21]. Its incorporation in the outer leaflet of the RBC membrane occurs with a tL of about 54 h [33], followed by a flip into the inner leaflet with an estimated ti of 2 h [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…A dramatic elevation in the choline concentration was observed in manic-depressive patients on lithium therapy in comparison with lithium-free patients and healthy volunteers [17][18][19][20]. Lithium ions inhibit the choline transport protein in RBC membranes, causing accumulation of choline [21]. The release of choline by a Ca2+-activated phospholipase from PC in haemolysates was first monitored using 'H spin-echo n.m.r.…”
Section: Introductionmentioning
confidence: 99%